HOW ANXIETY AFFECT ENGLISH ACHIEVEMENT?: A CORRELATIONAL STUDY OF INDONESIAN EFL LEARNERS - Nasution, Riandry Fadilah; Manuas, Maissy J.; Ali, Muhammad I.; Pabur, Herminus E.; Tatipang, Devilito P. (Journal of English Culture, Language, Literature and Education, 2022)
English is the language of communication used throughout the world the ability to speak English is the main priority of many languages studied by students today One of the factors that prevent students from speaking English is anxiety This study aims to determine the level of students anxiety in learning English the level of anxiety of students academic achievement and the relationship between students anxiety with the process of learning English and their achievement in the learning process The method used in this study is qualitative with a descriptive approach This study was conducted to 41 students of grade XI of X enrolled in the second semester of academic year Results showed that the students anxiety in learning English was moderate M=3 17 and their English academic achievement was categorized as failed M=70 98 Finally it was found that there was a significant correlation between students anxiety in learning English and their English achievement as the result p < em>= 00 lt;0 05 r< em>= 98 Therefore it is recommended that teachers try to find more creative methods and strategies to support and motivate the students in learning English< p>